Speaking for ourselves: autism and barriers to early intervention services in Cape Town - Bartlett, Kristin (Department of Sociology, 2020)
There is limited knowledge about autism as a disability in Africa: thus far, most autism research studies have been limited to families in high-income western countries, resulting in a gap in research regarding studies from low-income countries. Despite their vulnerability, people with disabilities have been largely unnoticed as a goal of development work despite disability’s economic impact on families and communities, and the associated discrimination, stigmatisation and exclusion. Education has been identified as an essential building block of human and economic development, yet children with disabilities face unequal barriers in accessing educational services and schooling. Focusing on early intervention services is vital for the growth and development of children with disabilities, as early human development services and programmes for young children and families play a critical role in alleviating poverty and achieving social and economic equity. The aim of this study was to identify the major barriers to accessing early intervention services for autistic individuals in Cape Town and achieving well-being. I drew on Sen’s capability approach to inform my theoretical framework. I used an embedded mixed methods design, with a quantitative questionnaire playing a supportive secondary role in this qualitative study, which included in-depth interviews and some documentary research. The sample consisted of ten participants: five parents of autistic children, and five autistic adults. Qualitative data for this study was analysed using thematic analysis, informed by Miles and Huberman’s (1994) process of first and second-level coding. The quantitative data for descriptive statistics was recorded and analysed using Statistical Package for the Social Sciences (SPSS). This study brought six themes into focus, namely services, financial constraints, practitioners, home environment, stigma, and lack of support services. A variety of recommendations were highlighted by the participants, including an adaptation of services; developing better trained practitioners in autism-specific strategies; making increased parent-training and support services available; together with creating a better system to help support, monitor and guide families and autistic individuals in navigating the field of services.